2005
DOI: 10.1128/jcm.43.2.996-998.2005
|View full text |Cite
|
Sign up to set email alerts
|

Nalidixic Acid-Resistant Salmonella enterica Serotype Typhi Presenting as a Primary Psoas Abscess: Case Report and Review of the Literature

Abstract: We report an unusual case of Salmonella enterica serotype Typhi presenting as a primary psoas abscess. The isolate tested susceptible to ciprofloxacin but resistant to nalidixic acid in vitro, a pattern associated with fluoroquinolone therapeutic failures. We review the literature for serovar Typhi psoas abscess in the absence of bacteremia and discuss the importance of identifying isolates with reduced susceptibility to fluoroquinolones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…Although clinical failures to treat nalidixic acid-resistant Shigella infection with fluoroquinolones have not been reported, clinicians should be aware that failures have been reported for Salmonella infections caused by strains that were resistant to nalidixic acid and had decreased susceptibility to ciprofloxacin (13,40).…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical failures to treat nalidixic acid-resistant Shigella infection with fluoroquinolones have not been reported, clinicians should be aware that failures have been reported for Salmonella infections caused by strains that were resistant to nalidixic acid and had decreased susceptibility to ciprofloxacin (13,40).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Vi antigen may be important in the survival of the bacterium within macrophages though this may not be in cellular invasion of the macrophage or the intestinal wall (14,30). Unlike most other serovars, Salmonella typhi expresses the Vi polysaccharide capsule, an important virulent factor.…”
Section: Molecular and Biologic Features Of Salmonella Typhimentioning
confidence: 99%
“…Studies conducted in the 1990s revealed significant increases in resistance to the most frequent antibiotic used against Salmonella, nalidixic acid (48). As the clinical outcome for patients infected with resistant strains is poor (13), new therapies must be sought out.…”
mentioning
confidence: 99%